"Evaluación de las semillas de dos variedades de aguacate (Persea Americana) para la obtención de tinta para su aprovechamiento en la agroindustria" - Romero Espinoza, Lenin Alexander (2017)
The project investigative realized is focused in establishing the parameters adapted for the obtaining ink for which in the present study It considered as aim: " To evaluate the seeds of two varieties of avocado (persea American), For the obtaining ink for his utilization in the agroindustry ". The experimental applied model consisted of a Design of Blocks with Arrangement factorial AxBxC with two repetitions is to say 8 treatments with 2 repetitions giving a total of 16 experimental units, to compare: Factor To varieties of avocado (V. Hass - V. Loudly), Factor B conditioning of the seed (Dehydrated - Without dehydrating) and Factor C Types of solvents (distilled water - hydroxide of sodium), for the separation of averages of the levels of the treatments did one come to the test of TUKEY's significance (p? 0.5). The analysis of information was realized by means of the statistical package STATGRAPHICS, to define quality parameters diverse analyses were realized as: pH, density, acidity, sensory analyses (Color - smell) applying the ink obtained in Fabric - Paper. The results indicate that the application of hydroxide of sodium like solvent used in this investigation allows to extract the intense coloraciomas. Obtaining the best results in pH the following tratamietos: T2 (hass + dehydrated + hydroxide of sodium), T4 (hass + without dehydrating + hydroxide of sodium), T6 (loudly + dehydrated + hydroxide of sodium) and the T8 (hass + without dehydrating + hydroxide of sodium). In what corresponds to Acidity one gave the best value T1 (hass + dehydrated + distilled water), Density did not exist it differentiates the information they are statistically equal. While to the sensory analyses realized to a group of panelists belonging to the Technical State University of Quevedo with regard to the color applied in fabric T1 (hass + dehydrated + distilled water), T2 (hass + dehydrated + hydroxide of sodium), T4 (hass + without dehydrating + hydroxide of sodium), T5 (loudly + dehydrated + distilled water), T6 (loudly + dehydrated + hydroxide of sodium) and T8 (loudly + without dehydrating + hydroxide of sodium). With relation to Smell (Fabric) difference did not exist, whereas in Color applied in (Paper) one gave better results T1 (hass + dehydrated + distilled water), T2 (hass + dehydrated + hydroxide of sodium); T6 (loudly + dehydrated + hydroxide of sodium) and T8 (loudly + without dehydrating + hydroxide of sodium). As for the Smell significant difference did not exist. Key words: seeds of avocado, ink, distilled water, hydroxide of sodium, dehydrate